Reciprocal Teaching and Comprehension of Struggling Readers - Humaira, Raslie; Damien, Mikeng; Ting, Su Hie (Macrothink Institute, 2015)
This preliminary study examined the effect of reciprocal teaching on struggling readers’ comprehension of a narrative text. The specific aspects studied were: (1) their suggestions to remake the ending of the narrative text based on preceding events; (2) their guided recall of details making up the gist of the narrative; and (3) their unguided recall of the gist of the narrative. The reciprocal teaching strategy was used to teach a literary text to 14 Malaysian struggling readers of English. The results showed that in the first lesson these students could not yet make links between the events of the story to suggest an alternative resolution of the narrative. Subsequently, their responses in the guided recall task showed that the four groups were able to supply the information making up gist of the story. However, the final unguided recall task showed that two groups usually provided their evaluation of their story and could remember only disparate details in the orientation of the story but could not recall major events. The findings suggest that a major challenge of implementing the reciprocal teaching strategy is guiding groups to share the task of monitoring their own comprehension through questioning, clarifying, summarizing and predicting.